2020
DOI: 10.3390/ijms21020482
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Induced Pluripotent Stem Cell Technologies to Understand Genetic Epilepsy

Abstract: The study of the pathomechanisms by which gene mutations lead to neurological diseases has benefit from several cellular and animal models. Recently, induced Pluripotent Stem Cell (iPSC) technologies have made possible the access to human neurons to study nervous system disease-related mechanisms, and are at the forefront of the research into neurological diseases. In this review, we will focalize upon genetic epilepsy, and summarize the most recent studies in which iPSC-based technologies were used to gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 113 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…Epilepsy-associated genes encode for ion channel and synaptic proteins, cell adhesion molecules, signaling proteins, and transcription factors. However, possible mutations in such different genes that can lead to epileptic seizures in most cases remain unclear [7][8][9]. The role of epigenetic modifications has been actively studied recently in the development of epilepsy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy-associated genes encode for ion channel and synaptic proteins, cell adhesion molecules, signaling proteins, and transcription factors. However, possible mutations in such different genes that can lead to epileptic seizures in most cases remain unclear [7][8][9]. The role of epigenetic modifications has been actively studied recently in the development of epilepsy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed [31] that in the Russian population (East Slavic ethnic group, the sample of individuals from 17 to 90 years old) UPS29 was represented by seven alleles, which differed not only in the number of repeats (6,8,9,10,14,17, and 24 ones) but also in combination of repeated units, as well as in the presence of deletions and/or single-nucleotide polymorphisms (SNPs) in DNA flanking minisatellite ( Figure 1 and Figure S2, Table S3). In the studied cohort, the allele of 17 repeats was predominant (91.5%), but the frequencies of other alleles were lower (from 0.3% to 4.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts were made to fuse spheroids or organoids of different cellular compositions to model more complex 3D brain structures (Birey et al 2017; Bagley et al, 2017) [ 51 , 114 ]. For example, Birey et al (2017) fused oligodendrocytes with an organoid consisting of GABAergic neurons and an organoid consisting of glutamatergic neurons and astrocytes [ 51 ].…”
Section: Approaches To Recreating Brain Complexity In Vitromentioning
confidence: 99%
“…Several attempts were made to fuse spheroids or organoids of different cellular compositions to model more complex 3D brain structures (Birey et al 2017; Bagley et al, 2017) [ 51 , 114 ]. For example, Birey et al (2017) fused oligodendrocytes with an organoid consisting of GABAergic neurons and an organoid consisting of glutamatergic neurons and astrocytes [ 51 ]. Using these conglomerate structures, the authors demonstrated the migration of GABA neurons from the ventral to the dorsal forebrain, their integration, and the formation of cortical nerve chains.…”
Section: Approaches To Recreating Brain Complexity In Vitromentioning
confidence: 99%
See 1 more Smart Citation